"But He Can't Be Gay": The Relationship between Masculinity and Homophobia in Father-Son Relationships. Issue 3 (October 2014) - Bucher, Jacob
In this article I explore how the father-son relationship impacts both the nature and extent of homophobia in men, specifically the difference in homophobic feelings a father has for his gay son compared to the homophobic feelings a son has for his gay father. The effect of masculinity, specifically hegemonic masculinity, on homophobia in men is well-documented and my goal is to continue this further given the role that fathers play in socializing/constructing masculinity for their sons and the role that sons play in constructing/validating masculinity for their fathers. Through surveys and interviews, measures of masculinity and homophobia were investigated among 100 men, ultimately providing insight into masculinity, homophobia, and the relationship between the two.